Pengaruh Komunikasi Interpersonal dan Motivasi Kerja terhadap Kepuasan Kerja Guru Yayasan SMA Angkasa Lanud Husein Sastranegara - Siska Salsabilla; Juddy Prabowo (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze the influence of interpersonal communication and work motivation on the job satisfaction of Angkasa Lanud Husein Sastranegara High School Foundation Teachers, Bandung City. This research uses quantitative methods. The data collection technique used was a questionnaire. The respondents of this research were 46 teachers. The measuring scale in this research uses semantic differential. The analysis used was multiple linear regression and determination with the help of SPSS version 26.0 software. The research results show that interpersonal communication and work motivation partially have a positive influence on teacher job satisfaction. In addition, interpersonal communication and work motivation simultaneously have an influence on the job satisfaction of the Angkasa Lanud Husein Sastranegara High School Foundation Teachers, Bandung City. Keywords: Interpersonal Communication, Work Motivation, Job Satisfaction